(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Diabetes Mellitus (DM) is a common metabolic disease due to absolute or relative insulin deficiency. Oxidative stress plays a major role in pathophysiology of type 2 DM and its prevalence is increased due to lifestyle and obesity. In past years different studies has been done to identify various oxidative stress markers. Aim of this study is to evaluate levels of serum Uric Acid (UA), Adenosine Deaminase (ADA), Fasting Plasma Glucose (FPG) and HbA1c in patients of Type 2 Diabetes Mellitus and healthy subject and also to find out role of UA and ADA as a marker of oxidative stress in type 2 DM. Material and methods: We measured the serum level of Uric Acid, ADA, HbA1c and FPG in 100 patients with type 2 diabetes and 50 healthy controls. Subjects included in study group were divided on the basis of duration of diabetes mellitus. Group 1 included subjects with type 2 DM < 1 year and Group 2 included subjects with type 2 DM > 5 year. Results: The difference in FPG, ADA and HbA1c were highly significant (p<0.05) in type 2 diabetic patients (< 1 year) in comparison to control group while the difference in uric acid is not significant in diabetes patients with < 1 year duration and healthy subjects. The difference in FPG, ADA, Uric Acid and HbA1c were highly significant (p<0.05) in type 2 diabetic patients (> 5-year duration) in comparison to control group. While comparing two diabetes groups difference in FPG, ADA, Uric Acid and HbA1c were also highly significant (p<0.05). Conclusion: Uric acid as a predictor of oxidative stress become significant as the duration of diabetes increases while ADA is statistically significant even during early onset of diabetes mellitus.